Hierarchical Dynamic Goal Management for IoT Systems - Axel Jantsch; Arman Anzanpour; Hedyeh Kholerdi; Iman Azimi; Lydia C. Siafara; Amir M. Rahmani; Nima TaheriNejad; Pasi Liljeberg; Nikil Dutt (United States, 2022)
As the Internet of Things (IoT) penetrates ever more application domains, many IoT-based systems are increasingly becoming more complex, versatile and resource-rich, and need to serve one or more applications with diverse and changing goals. These systems face new challenges in dynamic goal management due to a combination of limited shared resources, and multiple goals that may not only conflict with each other, but which may also change dynamically. We motivate the need for hierarchical, dynamic goal management for this class of complex IoT systems and substantiate our arguments with case studies from two application domains: patient health monitoring and Cyber-Physical Production Systems (CPPSs).
2018 19th International Symposium on Quality Electronic Design (ISQED)